Doenças mentais no ambiente urbano: um modelo investigativo na relação entre a epidemiologia social e a epidemiologia clássica - Teixeira, Fábio Derosso (2025)
The urbanization process, which involves the growth and development of urban areas, has been associated with significant impacts on people’s mental health. The relationship between the urban environment and mental illness is a complex and multifaceted issue that encompasses several interrelated factors. This study compares the application of theories of social epidemiology and classical epidemiology in mental illness care in health units, considering factors such as population density, basic sanitation, waste disposal, sanitary treatment, community groups, occupations, habitability and the impact of these factors on mental health care.Using data from the municipal health system, the aim is to establish connections between the two epidemiological theories by applying a classification model and a social simulation protocol. The proposed model was tested using open data from mental health services in the public health system of Curitiba, assigning weights to social variables and describing the findings in a social simulation protocol. As a result, it was possible to demonstrate how the epidemiological theories complement each other, paving the way for future studies and the application of other computational social simulation techniques in the urban context, aiming to facilitate the work of public managers.